Antifatigue Potential Activity of Sarcodon imbricatus in Acute Excise-Treated and Chronic Fatigue Syndrome in Mice via Regulation of Nrf2-Mediated Oxidative Stress. (28th June 2018) - Wang, Xue; Qu, Yidi; Zhang, Yongfeng; Li, Shaopeng; Sun, Yiyang; Chen, Zepeng; Teng, Lirong; Wang, Di
Abstract : Sarcodon imbricatus (SI), a precious edible fungus, contains 35.22% of total sugar, 18.33% of total protein, 24 types of fatty acid, 16 types of amino acid, and 8 types of minerals. Encouragingly, it is rich in potential antioxidants such as total polyphenols (0.41%), total sterols (3.16%), and vitamins (0.44%). In the present study, the antifatigue properties of SI and its potential mechanisms of action were explored by the experiments on acute excise-treated mice and chronic fatigue syndrome (CFS) mice. SI (0.25, 0.5, and 1 g/kg) significantly enhanced exercise tolerance in the weight-loaded forced swimming test (FST) and rota-rod test (RRT) and reduced the immobility in the tail suspension test on CFS mice. SI markedly increased the levels of glycogen in the liver and adenosine triphosphate (ATP) in the liver and muscle and decreased the lactic acid (LD) and blood urea nitrogen (BUN) content in both acute swimming-treated mice and CFS mice. SI improved the endogenous cellular antioxidant enzyme contents in the two mouse models by improving the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and reducing reactive oxygen species (ROS) and malondialdehyde (MDA) levels in serum, liver, and muscle, respectively. In CFS mice, the enhanced expression levels of nuclear factor erythroid-2-related factor 2 (Nrf2), SOD1, SOD2, heme oxygenase-1 (HO-1), and catalase (CAT) in the liver were observed after a 32-day SI administration. Our data indicated that SI possessed antifatigue activity, which may be related to its ability to normalize energy metabolism and Nrf2-mediated oxidative stress. Consequently, SI can be expected to serve as a novel natural antifatigue supplement in health foods.